Rural dwellers are less likely to survive cancer – An international review and meta-analysis. (September 2018) - Carriere, Romi; Adam, Rosalind; Fielding, Shona; Barlas, Raphae; Ong, Yuhan; Murchie, Peter
Abstract: Background: Existing research from several countries has suggested that rural-dwellers may have poorer cancer survival than urban-dwellers. However, to date, the global literature has not been systematically reviewed to determine whether a rural cancer survival disadvantage is a global phenomenon. Methods: Medline, CINAHL, and EMBASE were searched for studies comparing rural and urban cancer survival. At least two authors independently screened and selected studies. We included epidemiological studies comparing cancer survival between urban and rural residents (however defined) that also took socioeconomic status into account. A meta-analysis was conducted using 11 studies with binary rural:urban classifications to determine the magnitude and direction of the association between rurality and differences in cancer survival. The mechanisms for urban-rural cancer survival differences reported were narratively synthesised in all 39 studies. Findings: 39 studies were included in this review. All were retrospective observational studies conducted in developed countries. Rural-dwellers were significantly more likely to die when they developed cancer compared to urban-dwellers (HR 1.05 (95% CI 1.02 – 1.07). Potential mechanisms were aggregated into an ecological model under the following themes: Patient Level Characteristics; Institutions; Community, Culture and Environment; Policy and Service Organization. Interpretation: Rural residents were 5% less likely to survive cancer. This effect was consistently observed across studies conducted in various geographical regions and using multiple definitions of rurality. High quality mixed-methods research is required to comprehensively evaluate the underlying factors. We have proposed an ecological model to provide a coherent framework for future explanatory research. Funding: None. Highlights: Retrospective observational studies conducted in developed countries comparing urban and rural cancer survival and related outcomes. Increased risk in cancer death among rural/remote patients. Establishment of a theoretical framework to illustrate factors influencing cancer survival in these geographical regions. Support for further research on these themes.